Transfusion as an Inflammation Hit: Knowns and Unknowns - Garraud, Olivier; Tariket, S.; Sut, C.; Haddad, A.; Aloui, C.; Chakroun, T.; Laradi, S.; Cognasse, F. (Frontiers in Immunology, 2016)
Transfusion of blood cell components is frequent in the therapeutic arsenal; it is globally safe or even very safe. At present, residual clinical manifestations are principally inflammatory in nature. If some rare clinical hazards manifest as acute inflammation symptoms of various origin, most of them linked with conflicting and undesirable biological material accompanying the therapeutic component (infectious pathogen, pathogenic antibody, unwanted antigen or allergen), the general feature is subtler and less visible, and essentially consists of alloimmunization or febrile non haemolytic transfusion reaction. The present essay aims to present updates in haematology and immunology that help understand how, when and why subclinical inflammation underlies alloimmunization, and circumstances characteristic of red blood cells and—even more frequently—platelets that contribute inflammatory mediators. Modern transfusion medicine makes sustained efforts to limit such inflammatory hazards; efforts can be successful only if one has a clear view of each element’s role.